Respuesta :
Answer:
x = 5/2
x = 2 1/2
x = 2.5
Step-by-step explanation:
3x - 1 - (x + 3) = 1
3x - 1 - x - 3 = 1
2x - 1 - 3 = 1
2x - 4 = 1
2x = 1 + 4
2x + 5
2x = 5
x = 5/2 → 2 1/2 → 2.5 ( can be written in any of these forms depending on what you need to do)
Hope this helped! :)
Answer:
x = 5/2
Step-by-step explanation:
3x−1−(x+3)=1
First remove the bracket
That's
3x - 1 - x - 3 = 1
Group the constants at the right side of the equation
That's
3x - x = 1 + 1 + 3
Simplify
We have
2x = 5
Divide both sides by 2
That's
2x / 2 = 5/2
x = 5/2
Hope this helps you